1995
DOI: 10.1002/mds.870100517
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better definition of the restless legs syndrome

Abstract: A large International Restless Legs Syndrome (RLS) Study Group has been formed. As its first task, the group has taken upon itself the role of defining the clinical features of the RLS. As minimal criteria for diagnosis, the group proposes the following four features: (a) desire to move the extremities, often associated with paresthesias/dysesthesias; (b) motor restlessness; (c) worsening of symptoms at rest with at least temporary relief by activity, and (d) worsening of symptoms in the evening or night. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
237
4
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 990 publications
(254 citation statements)
references
References 85 publications
(7 reference statements)
4
237
4
9
Order By: Relevance
“…The present case, however, does not fulfill the minimal criteria for this syndrome, according to the International Restless Legs Syndrome Study Group [7], in which the patient shows no apparent urge to move the legs, no motor restlessness, no significant change with rest or action, and no apparent worsening with sleep. The few cases involv- …”
Section: Discussioncontrasting
confidence: 67%
“…The present case, however, does not fulfill the minimal criteria for this syndrome, according to the International Restless Legs Syndrome Study Group [7], in which the patient shows no apparent urge to move the legs, no motor restlessness, no significant change with rest or action, and no apparent worsening with sleep. The few cases involv- …”
Section: Discussioncontrasting
confidence: 67%
“…The IRLS is a 10-item questionnaire that measures two dimensions of restless legs syndrome (symptoms and symptoms impact); each item is rated on a four-point scale (0 = none to 4 = very severe), and total score is a sum of the individual item scores (mild = 1-10 points; moderate = 11-20 points; severe = 21-30 points; and very severe = 31-40 points). Because one-third of patients with fibromyalgia also have restless legs syndrome and studies have demonstrated symptomatic improvement with ferric carboxymaltose [19], study patients were screened for this disorder [20,21] and the IRLS was used as a potential explanatory factor for observed changes from baseline in Revised Fibromyalgia Impact Questionnaire (FIQR) [22] scores.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Recognition of RLS as an important clinical condition is growing, in part aided by standardized diagnostic criteria developed by international expert consensus in 1995 3 and revised in 2002. 4 RLS is characterized by a compelling urge to move the legs that is usually accompanied by uncomfortable, often painful sensations in the legs, begins or worsens during periods of inactivity, is worse during the evening and nighttime hours, and is partially or totally relieved by movement.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%